B Cell Activating Factor (BAFF) and a Proliferation Inducing Ligand (APRIL) Mediate CD40‐Independent Help by Memory CD4 T Cells. Issue 2 (12th December 2014) - Gorbacheva, V.; Ayasoufi, K.; Fan, R.; Baldwin, W. M.; Valujskikh, A.
<x xml:space="preserve">Abstract</x> Donor‐reactive memory T cells undermine organ transplant survival and are poorly controlled by immunosuppression or costimulatory blockade. Memory CD4 T cells provide CD40‐independent help for the generation of donor‐reactive effector CD8 T cells and alloantibodies (alloAbs) that rapidly mediate allograft rejection. The goal of this study was to investigate the role of B cell activating factor (BAFF) and a proliferation‐inducing ligand (APRIL) in alloresponses driven by memory CD4 T cells. The short‐term neutralization of BAFF alone or BAFF plus APRIL synergized with anti‐CD154 mAb to prolong heart allograft survival in recipients containing donor‐reactive memory CD4 T cells. The prolongation was associated with reduction in antidonor alloAb responses and with inhibited reactivation and helper functions of memory CD4 T cells. Additional depletion of CD8 T cells did not enhance the prolonged allograft survival suggesting that donor‐reactive alloAbs mediate late graft rejection in these recipients. This is the first report that targeting the BAFF cytokine network inhibits both humoral and cellular immune responses induced by memory CD4 T cells. Our results suggest that reagents neutralizing BAFF and APRIL may be used to enhance the efficacy of CD40/CD154 costimulatory blockade and improve allograft survival in T cell–sensitized recipients.